Ultrastructural Analysis of Leishmania infantum chagasi Promastigotes Forms Treated In Vitro with Usnic Acid. (12th February 2015) - da Luz, João S. B.; de Oliveira, Erwelly B.; Martins, Monica C. B.; Silva, Nicácio H. da; Alves, Luiz C.; dos Santos, Fábio A. B.; da Silva, Luiz L. S.; Silva, Eliete C.; de Medeiros, Paloma L.
Abstract : Leishmaniasis is considered by the World Health Organization as one of the infectious parasitic diseases endemic of great relevance and a global public health problem. Pentavalent antimonials used for treatment of this disease are limited and new phytochemicals emerge as an alternative to existing treatments, due to the low toxicity and cost reduction. Usnic acid is uniquely found in lichens and is especially abundant in genera such as Alectoria, Cladonia, Evernia, Lecanora, Ramalina, and Usnea . Usnic acid has been shown to exhibit antiviral, antiprotozoal, antiproliferative, anti-inflammatory, and analgesic activity. The aim of this study was to evaluate the antileishmanial activity of usnic acid on Leishmania infantum chagasi promastigotes and the occurrence of drug-induced ultrastructural damage in the parasite. Usnic acid was effective against the promastigote forms (IC50 = 18.30 ± 2.00  µ g/mL). Structural and ultrastructural aspects of parasite were analyzed. Morphological alterations were observed as blebs in cell membrane and shapes given off, increasing the number of cytoplasmic vacuoles, and cellular and mitochondrial swelling, with loss of cell polarity. We concluded that the usnic acid presented antileishmanial activity against promastigote forms of Leishmania infantum chagasi and structural and ultrastructural analysis reinforces its cytotoxicity. Further, in vitro studies are warranted to further evaluate this potential.